Impact of Early Follow-Up on Readmissions in Chronic Hypercapnic Respiratory Failure Patients on Non-Invasive Ventilation Therapy - Christopher Lau; Armeen Mehrabani; Deandra Kuruppu; Jayen Sum; Karim El-Kersh; Joyce Lee-Iannotti; Kenneth Knox; Daniel Puebla Niera (Observations and Insights in Pulmonary and Critical Care, 2026)
Study Objectives Acute on chronic hypercapnic respiratory failure is a severe manifestation of multiple disease pathways, including but not limited to primary pulmonary diseases, obesity hypoventilation syndrome, and neuromuscular diseases. It is associated with high mortality, increased healthcare utilization, and frequent hospital readmissions. Although inpatient noninvasive ventilation (NIV) often improves gas exchange in the acute hospital setting, persistent hypercapnia commonly necessitates continuation of NIV after discharge. Long-term NIV improves survival, quality of life, and reduces exacerbations, yet structured early follow-up remains inconsistent. This study characterizes the transition-of-care practices at a large tertiary academic medical center for patients with chronic hypercapnic respiratory failure. Methods A retrospective cohort study was conducted at a tertiary academic medical center between December 1, 2023, and April 1, 2025. The population consisted of adults who presented with hypercapnic respiratory failure and were prescribed non-invasive ventilation on discharge. Electronic health records were reviewed for demographics, underlying diagnoses, prior hospitalizations, outpatient follow-up within 30 days, and 30-day readmission outcomes. Patients who completed timely follow-up were compared with those who did not. Results Seventy-one patients were included. Obesity hypoventilation syndrome (77%) and COPD (20%) were the predominant etiologies. Only 29 patients (40.8%) completed outpatient follow-up within 30 days. Those who received timely follow-up had significantly lower 30-day readmission rates compared with those without follow-up (10.3% vs 45.2%). Additionally, 45% of the cohort experienced at least one hospitalization in the year preceding NIV initiation, totaling 76 hospitalizations, indicating substantial baseline healthcare utilization. Conclusions Among patients newly initiated on home NIV for chronic hypercapnic respiratory failure, early outpatient follow-up was strongly associated with reduced 30-day readmission rates. Structured post-discharge evaluation may be a critical yet underutilized component of transitional care and a potential target for improving outcomes in this high-risk population.